Minute lesions of alveolar damage in lungs of patients with stable idiopathic pulmonary fibrosis. Issue 1 (8th February 2015) - Emura, Iwao; Usuda, Hiroyuki; Togashi, Kenichi; Satou, Kazuhiro
<x xml:space="preserve">Abstract</x> Aims To investigate the mechanisms underlying the acute exacerbation of idiopathic pulmonary fibrosis, and in particular the role of minute lesions of alveolar damage. Methods and results We examined surgical lung biopsy samples from 38 patients with stable idiopathic pulmonary fibrosis, and evaluated the association between the foci and development of acute exacerbation. Mild extravasation, probably resulting from lung injury and intra‐alveolar oedema fluid, were observed in narrow areas of architecturally intact lung tissue. Minute lesions of alveolar damage were detected in these areas. Alveolar epithelial cells in these lesions were injured. Hypoxia‐inducible factor‐2α‐positive macrophages, tumour necrosis factor‐α‐positive macrophages and neutrophils had accumulated in alveolar spaces in and around these lesions. Cases were classified into patients without (17) and with (21) minute lesions of alveolar damage. Development to acute exacerbation (five cases) occurred only in patients with minute lesions of alveolar damage (P = 0.03). Conclusions The formation of minute lesions of alveolar damage may be initiated by hypoxia, and such lesions play important roles in the development of acute exacerbation.